ANALYSIS OF TRIGGER EVENT, EXPLORATION, INTEGRATION, AND RESOLUTION SKILLS OF PHYSICS EDUCATION STUDENTS IN SOLVING THERMODYNAMICS PROBLEMS - Farcis, Fenno; Budi, Gunarjo S. (Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
Critical thinking skills are skills that must be had by science teachers in the current 4.0 industrial revolution era. Indicators of critical thinking skills that must be possessed include trigger events, namely identifying problems, exploring thinking about personal and social ideas in order to make a decision preparation, integration that is constructing the intent/meaning of an idea, and integrating relevant information that has been set at the exploration stage, and Resolution is implementing and testing a solution. This research was conducted to determine the critical thinking skills of physics education students in solving problems in lectures on thermodynamics. The research sample were 30 physics education students at the Faculty of Teacher Training and Education, Universitas Palangka Raya who programmed the Thermodynamics Course and taken randomly. Evaluation of critical thinking skills consists of 8 questions that ask students to complete in a structured manner. The results showed that by applying the critical thinking skills evaluation instrument students had: 55% trigger event skills with low criteria, 45% exploration skills with very low criteria, 35% integration skills with very low criteria and 30% resolution skills with very low criteria. The results of this study are the basis for recommending the need for a learning model or approach that can be implemented in thermodynamic lectures to improve the critical thinking skills of trigger events, exploration, integration, and resolution of physics education students.